Immunogenicity, reactogenicity and safety of 2 doses of an adjuvanted herpes zoster subunit vaccine administered 2, 6 or 12 months apart in older adults: Results of a phase III, randomized, open-label, multicenter study. Issue 1 (2nd January 2018) - Lal, Himal; Poder, Airi; Campora, Laura; Geeraerts, Brecht; Oostvogels, Lidia; Vanden Abeele, Carline; Heineman, Thomas C.
Highlights: 2 doses of HZ/su 2 months apart were immunogenic and efficacious against HZ. We assessed humoral immunogenicity of 2 HZ/su doses given 6 or 12 months apart. Humoral immunogenicity of the 0, 6-month schedule was non-inferior to the 0, 2-one. Non-inferiority of the 0, 12- to the 0, 2-month schedule was not demonstrated. No safety concerns were identified for any of the schedules. Abstract: Background: In phase III trials, 2 doses of a herpes zoster (HZ) subunit vaccine (HZ/su; 50 µg varicella-zoster virus glycoprotein E [gE] and AS01B Adjuvant System) administered 2-months apart in older adults (≥50 and ≥70 years) demonstrated >90% efficacy in preventing HZ and had a clinically acceptable safety profile. Here we report immunogenicity, reactogenicity and safety following administration of 2 HZ/su doses at intervals longer than 2 months. Methods: In this Phase III, open-label trial conducted in the US and Estonia, 354 adults ≥50 years were randomized 1:1:1 to receive 2 HZ/su doses 2, 6, or 12 months apart. gE-specific humoral immune responses were evaluated at pre-vaccination, 1 and 12 months post-dose 2. Co-primary objectives were to compare immune responses to HZ/su 1 month post-dose 2 when given 6-months or 12-months apart to those administered 2-months apart. For each participant, safety information was collected from dose 1 to 12 months post-dose 2. Results: 346 participants completed the study and 343 were included in the according-to-protocol cohort for immunogenicity. One month post-dose 2, vaccine response rates were 96.5% (97.5% confidence interval [CI]: 90.4; 99.2) and 94.5% (97.5% CI: 87.6; 98.3) for the 0, 6- and 0, 12-month schedules, respectively, both schedules meeting the pre-defined criterion. Non-inferiority of anti-gE geometric mean concentrations was demonstrated for HZ/su administered on 0, 6-month compared to a 0, 2-month schedule; however, HZ/su administered on a 0, 12-month schedule did not meet the non-inferiority criterion. Injection site pain was the most commonly reported solicited adverse event (AE). 26 participants each reported at least 1 serious AE; none were assessed as related to vaccination. Conclusions: Immune responses to HZ/su administered at 0, 6-month were non-inferior to those elicited by a 0, 2-month schedule. HZ/su exhibited a clinically acceptable safety profile for all dosing intervals. Clinical Trials Registration: Clinicaltrials.gov (NCT01751165 ).